Role of different methods of contraception and time of menstrual cycle on dry socket - Abid, Sidra; Khan, Javeria; Hameed, Uzma; Mohsina Marufi; Charania Sheikh, Amynah (Journal of the Pakistan Medical Association, 2025)
Objectives: To investigate the potential association between the use of contraceptives and the occurrence of dry socket following tooth extraction. Method: The cross-sectional study was conducted at the Dow International Dental College, Karachi, from April to October 2023, and comprised female patients aged 18-45 years who underwent posterior maxillary and mandibular tooth extractions. All the extractions were conducted under local anaesthesia by the same surgeon. After extraction, the patients were given preventive anti-inflammatories and prophylactic antibiotics. Extraction success was the dependent variable, while contraceptive use was the independent variable, and the association between the two was evaluated. Data was analysed using SPSS 21. Results: Of the 193 female subjects, female patients aged 18-45 years 68(35.2%) were in the follicular phase of their menstrual cycle, 106(54.9%) were in the luteal phase, and 19(9.8%) were in the ovulation phase. Regarding contraceptive methods, 133(68.9%) used oral contraceptive pills, followed by 28(14.5%) using combined oral contraceptive pills. The development of dry socket was observed in 61(31.6%) cases. A significant positive correlation was found between oral contraceptive use and an increased risk of dry socket (p<0.05). Women in the luteal phase had significantly higher odds of developing dry socket compared to those in the ovarian phase (p=0.029), while the odds of developing dry socket during the follicular phase were significantly lower compared to the ovarian phase (p=0.001). Conclusion: There is a need to take oral contraceptives usage into account as a possible contributory factor for socket dryness in female dental extraction patients. Key Words: Alveolar osteitis, Contraceptive agents, Menstrual cycle, Dry socket, Oral contraceptives.